Size-dependent deformation mechanism transition in titanium nanowires under high strain rate tension. (15th November 2017) - Chang, Le; Zhou, Chang-Yu; Pan, Xiang-Ming; He, Xiao-Hua
Abstract: Tensile deformation of single crystal titanium nanowires (NWs) with size ranging from 3 nm to 20 nm along [0001] orientation is investigated by molecular dynamics (MD) simulations. For all NWs, the initial yielding at different strain rates is induced by the nucleation of 10 1 ¯ 2 twinning. Following the saturation of twin volume fraction, the size dependent transition of deformation mechanisms in twinned regions is observed. At the strain rate from 10 8  s − 1 to 10 9  s − 1, following the deformation twinning, the phase transformation from HCP to FCC dominates the plastic deformation of Ti NWs. By increasing sample size to 20 nm, phase transformation can be replaced by prismatic dislocation slip. At the strain rate from 10 9  s − 1 to 10 10  s − 1, the critical size for the transition from phase transformation to full dislocation slip decreases with the applied strain rate. With further increasing sample size, after the saturation of 10 1 ¯ 2 twins, the initial single crystal NW transforms to nanocrystalline NW. Subsequent plastic deformation mechanism in the nanocrystalline Ti NW with large size is transferred from grain boundary dominate deformation to the cooperation of grain boundary deformation and dislocation activity. Furthermore, deformation mechanism map is proposed to provide a deep understanding of the plastic deformation of Ti NWs. Graphical abstract: Highlights: Sample size-dependent strain rate sensitivity was found. The incipient plasticity is induced by 10 1 ¯ 2 extension twinning. The tendency of phase transformation decreases with sample size and strain rate. Dislocation activity increases with sample size in the post-twinned nanocstalline samples.